Implementasi Algoritma Welch-Powell pada Pembagian Lokasi Kantor Cabang dalam Pemeriksaan Pipa Perumda Tirta Batang Hari - Nurul Hasanah (INDO PUBLISHING, 2026)
PERUMDA Air Minum Tirta Batang Hari conducts routine inspections of pipeline connections and water pumps at branch offices to maintain the continuity of clean water distribution. The large number of inspection locations and the varying distances between branch offices result in inefficient technician route allocation. This study aims to model routine inspection locations into a graph and determine a more optimal route allocation using the Welch-Powell Algorithm. The data used are secondary data in the form of locations and distances among 13 branch offices of PERUMDA Tirta Batang Hari obtained through Google Maps. The research method was carried out by constructing a graph based on adjacency relationships between locations, determining the degree of each vertex, and applying the Welch-Powell Algorithm through a graph coloring process. The results showed that graph coloring produced a chromatic number of four colors, consisting of the blue group with vertices 8 and 9, the green group with vertices 12 and 13, the yellow group with vertices 10, 7, and 6, and the orange group with vertices 1, 2, 11, 3, 4, and 5. These results indicate that the Welch-Powell Algorithm can be applied to assist the grouping of routine inspection locations so that technician route allocation becomes more organized and efficient.